CD28 activation pathway regulates the production of multiple T-cell-derived lymphokines/cytokines. - Thompson, C B (1989)
CD28 is a 44-kDa glycoprotein expressed as a homodimer on the surface of a major subset of human T cells. Previous studies have demonstrated that the binding of monoclonal antibodies to the CD28 surface antigen can augment the proliferation of purified human T cells stimulated with suboptimal doses of mitogens or anti-T-cell receptor/CD3 complex antibodies. In this report, we show that CD28 stimulation augments T-cell immune responses by specifically inducing a 5- to 50-fold enhancement in the expression and secretion of interleukin 2, tumor necrosis factor type alpha, lymphotoxin, interferon gamma, and granulocyte-macrophage colony-stimulating factor in normal human T cells stimulated to proliferate by crosslinking of the T-cell receptor/CD3 complex. This CD28-mediated induction of lymphokine/cytokine gene expression occurred even in T cells stimulated with optimal concentrations of mitogens or anti-T-cell receptor/CD3 antibodies, although under these conditions CD28 activation failed to enhance the proliferative response. The activation pathway induced by stimulation of CD28 is distinct from other biochemical pathways that induce lymphokines/cytokines because CD28 stimulation can induce lymphokine/cytokine gene expression in the presence of the immunosuppressant cyclosporine. Together these data suggest that the CD28 cell surface molecule is part of a distinct activation pathway that specifically modulates the expression of multiple lymphokine/cytokine genes.